Model Family Centered Maternity Care sebagai Strategi Optimalisasi Competent Mothering - Asmuji Asmuji; Diyan Indriyani (Jurnal Ners, 2016)
Introduction: Indonesia’s rate of MMR and IMR remains high among other ASEAN countries. This issue needs to be seriously addressed, particularly in dealing the mother-and-infant related problems, through developing the postnatal education model which focuses on postpartum mother by involving family as the social support.Methods: This research is conducted at dr. Soebandi Regional Hospital Jember and the Kaliwates Primary Health Service Jember Regency. This research employs participative approach (qualitative) and Participatory Action Research (PRA), with the intention of conducting the try-out to the postnatal education model comprehensively, as well as evaluating the perfection attempts to the model in order to generate the fittest model. The data collection technique used in this research is survey/observation, interview, FGD, in-depth interview to postpartum mothers and family (100 respondents), as well as healthcare extension agents.Results: This research has successfully formulated the postnatal education model through FCMC approach as the optimization of competent mothering strategy in lowering the infant and maternal mortality rate. This model has undergone comprehensive trial to postpartum mothers and family as well as the healthcare extension agents by providing modules and booklet concerning the treatment of postpartum mother and newly born infants in accordance with the postpartum stages. The results of this research revealed that the effect of postnatal education model through the FCMC approach on the perception of postpartum mothers and their family regarding the self-care treatment during the immediately post partum period, the infant and self-care treatment at the early and late postpartum stages by using the α = 0,05 existed as shown by the p value of 0,00 each. Furthermore, there was also an impact of the extension attempt of postnatal education model through the FCMC towards the perception of the healthcare extension agents with the p value of 0,00.Conclusion:  This research recommended that the postnatal education model through family centered maternity care (FCMC) as the optimization of competent mothering is implemented as one of the attempts in lowering the Maternal and Infant Mortality Rates, respectively.